BARRIERS TO PHYSICAL FITNESS, HEALTHCARE AND FOOD SECURITY OF OLDER PERSONS AND COPING MECHANISMS TO DEAL WITH THE BARRIERS IN UGANDA - Nankwanga, Annet (Journal of Community and Health Sciences, 2020)
This paper explores the barriers to older people's physical fitness,healthcare, food security and nutrition and the coping mechanisms devised to deal with the barriers. This was a descriptive cross-sectional survey. The research was based on eight districts, which included: Pallisa, Kampala, Jinja, Lira, Nebbi, Ntungamo, Luwero and Mbarara district. These districts were representative of both the rural and urban areas of the four regions of Uganda, namely:Western, Northern, Eastern and Central region. The sample consisted of 165 older persons and 50 key infromants selected using purposive sampling. Data was collected using focus group discussions and in-depth interviews guided by focus-group discussion guide and interview guide, respectively. Additional data from the key informants was collected through interviews. Analysis was done using the thematic technique and the themes were developed according to the context and variables of the study. The themes were then coded and entered into SPSS software for analysis and frequency and percentage distributions were generated. Results indicate that bodily weaknesses constituted the barrier to the physical fitness of themajority (75.2%) of the older persons in Uganda. Other barriers included lack of space for physical exercises and money to pay to health clubs. In contrast, suffering from chronic illnesses prevented more (52.5%) of the rural-based older persons than to the urban-based older persons (29.7%). Regarding access to health services the barriers included Health workers' aloofness, lack of respect for older persons, long distances to health centers and unavailability of health workers at health centers. While the barrier to food security and nutrition desired by the overwhelming majority of older persons in both rural and urban areas was economic inability to afford a balanced diet. Concerning coping mechanism,most of the older persons in rural areas (97%) grew food to cope with food security and nutrition barriers, while most of those in urban areas (70.3%) bought the food frommarkets. Findings included in this paper indicate that the coping mechanisms devised by older persons in Uganda needed policy action to be effective.